Is there an association between the coverage of immunisation boosters by the age of 5 and deprivation?: an ecological study - Sandford, Helena; Tata, Laila J.; Browne, Ivan; Pritchard, Catherine (Elsevier, 2015)
Objective: To determine whether there was an association between the coverage of booster immunisation of Diphtheria, Tetanus, acellular Pertussis and Polio (DTaP/IPV) and second Measles, Mumps and Rubella (MMR) dose by age 5 in accordance with the English national immunisation schedule by area-level socioeconomic deprivation and whether this changed between 2007/08 and 2010/11. Design: Ecological study. Data: Routinely collected national Cover of Vaccination Evaluated Rapidly data on immunisation coverage for DTaP/IPV booster and second MMR dose by age 5 and the Index of Multiple Deprivation (IMD). Setting: Primary Care Trust (PCT) areas in England between 2007/08 and 2010/11. Outcome Measures: Population coverage (%) of DTaP/IPV booster and second MMR immunisation by age 5. Results: Over the 4 years among the 9,457,600 children there was an increase in the mean proportion of children being immunised for DTaP/IPV booster and second MMR across England, increasing from 79% (standard deviation (SD12%)) to 86% (SD8%) for DTaP/IPV and 75% (SD10%) to 84% (SD6%) for second MMR between 2007/08 and 2010/11. In 2007/08 the area with lowest DTaP/IPV booster coverage was 31% compared to 54.4% in 2010/11 and for the second MMR in 2007/08 was 39% compared to 64.8% in 2010/11. A weak negative correlation was observed between average IMD score and immunisation coverage for the DTaP/IPV booster which reduced but remained statistically significant over the study period (r = −0.298, p<0.001 in 2007/08 and r = −0.179, p = 0.028 in 2010/11). This was similar for the second MMR in 2007/08 (r = −0.225, p = 0.008) and 2008/09 (r = −0.216, p = 0.008) but there was no statistically significant correlation in 2009/10 (r = −0.108, p = 0.186) or 2010/11 (r = −0.078, p = 0.343). Conclusion: Lower immunisation coverage of DTaP/IPV booster and second MMR dose was associated with higher area-level socioeconomic deprivation, although this inequality reduced between 2007/08 and 2010/11 as proportions of children being immunised increased at PCT level, particularly for the most deprived areas. However, coverage is still below the World Health Organisation recommended 95% threshold for Europe.